Applicability of the five case model to African eHealth investment decisions - Sean C. Broomhead; Maurice Mars; Richard E. Scott; Tom Jones (BMC, 2020)
Abstract Background eHealth programmes in African countries face fierce competition for scarce resources. Such initiatives should not proceed without adequate appraisal of their probable impacts, thereby acknowledging their opportunity costs and the need for appraisals to promote optimal use of available resources. However, since there is no broadly accepted eHealth impact appraisal framework available to provide guidance, and local expertise is limited, African health ministries have difficulty completing such appraisals. The Five Case Model, used in several countries outside Africa, has the potential to function as a decision-making tool in African eHealth environments and serve as a key component of an eHealth impact model for Africa. Methods This study identifies internationally recognised metrics and readily accessible data sources to assess the applicability of the model's five cases to African countries. Results Ten metrics are identified that align with the Five Case Model's five cases, including nine component metrics and one summary metric that aggregates the nine. The metrics cover the eHealth environment, human capital and governance, technology development, and finance and economics. Fifty-four African countries are scored for each metric. Visualisation of the metric scores using spider charts reveals profiles of the countries' relative performance and provides an eHealth Investment Readiness Assessment Tool. Conclusion The utility of these comparisons to strengthen eHealth investment planning suggests that the five cases are applicable to African countries' eHealth investment decisions. The potential for the Five Case Model to have a role in an eHealth impact appraisal framework for Africa should be validated through field testing.